Where did interpretivism go in the theory of entrepreneurship? - Packard, Mark D. (Journal of Business Venturing, 2017)
I argue that an interpretivist philosophic approach has been neglected in modern entrepreneurship research, but that such an approach may be most appropriate to the individualist nature of entrepreneurship. Realist meta-theories suffer from issues of paradigm incommensurability that may be at the heart of the present difficulties in defining and delineating the field of entrepreneurship. Interpretivism offers a potentially groundbreaking philosophical alternative that highlights the source of entrepreneurship in individuals rather than in abstract markets, emphasizing emergence rather than presuming opportunity existence. In this paper I defend interpretivism against its critics and revisit the nature of entrepreneurship through this lens. I show that process theories of entrepreneurship are aligned with interpretivist meta-theory, and that their explicit adoption of an interpretivist foundation may better facilitate theoretical progress.